Recycled aggregate-containing high-strength anti-crack mortar for 3D printing and preparation method of recycled aggregate-containing high-strength anti-crack mortar
By using high-strength crack-resistant mortar containing regenerated aggregate in 3D printed building slurry, and using modified lightweight aggregate to replace part of regenerated aggregate, the problem of high density of 3D printed building slurry is solved and higher flow is achieved and build performance and maintain good mechanical properties.
Patent Information
- Application Number
- CN202411432170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing 3D printing building slurry density is high, which leads to a large burden on printing equipment and high energy consumption. The printed building components are too heavy, making it difficult to print the suspended structure.
High-strength crack-resistant mortar containing recycled aggregates, and its formula includes cement, recycled aggregates, modified light aggregates, fly ash, biomass ash, alkali triggers, reinforcing fibers and retarding water reducers. Lightweight aggregates replace partially regenerated aggregates, improve the fluidity of the mortar and reduce the density of concrete.
Effectively reduce the density of 3D printed building slurry, improve its fluidity and construction performance, making it more suitable for 3D printed buildings, while maintaining more than 80% of the mechanical strength, with good compressive strength and flexural strength .
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing building materials, and in particular to a high-strength crack-resistant mortar for 3D printing containing recycled aggregate and a preparation method thereof. Background Art
[0002] As part of the fourth industrial revolution, 3D printing technology has gradually penetrated into the construction industry in recent years. 3D printing construction technology is a new type of construction technology, which mainly realizes the construction of building entities by converting digital building models into printing paths and controlling the extrusion of building materials layer by layer. 3D printing construction technology is also considered to be a technology that can promote the transformation and upgrading of the construction industry due to its shorter production time, lower labor allocation, and powerful complex structure design capabilities. At the same time, in the past few decades, people have paid a lot of attention to the sustainability of the built environment. How to integrate the concept of sustainable development into the concept of 3D printing and reuse construction waste under the conditions of protecting the environment and ecological safety is becoming a very important research content.
[0003] As non-renewable natural resources such as river sand and gravel become scarce due to high consumption in construction, crushing waste concrete and adding it as recycled aggregate to newly prepared concrete has become a feasible way to deal with this problem. Moreover, combining 3D printing construction technology with environmentally friendly polymers and supplementing it with the reuse of construction solid waste can not only improve the utilization rate of construction solid waste, solve the problems of scarce natural sand and gravel resources and the increasing production of construction solid waste year by year, but also reduce carbon emissions in the construction production process and develop a green circular economy.
[0004] At present, the 3D printing concrete slurry required for 3D printing buildings needs to have specific working properties compared to ordinary concrete slurry, such as certain fluidity and construction properties (stable after extrusion). However, the density of common 3D printing concrete slurry is close to that of ordinary concrete, usually around 2000kg / m 3 The above, on the one hand, creates a heavy load, which not only requires a high load-bearing capacity of the printing equipment, but also requires higher energy consumption during stirring, pumping, print nozzle movement and extrusion; on the other hand, the printed building components may be too heavy, making it difficult to print some suspended structures. Summary of the invention
[0005] In order to reduce the density of 3D printed building slurry while maintaining high material mechanical properties and construction performance after curing, and further improve the comprehensive performance of 3D printed concrete slurry, the present application provides a high-strength crack-resistant mortar for 3D printing containing recycled aggregate and a preparation method thereof.
[0006] In the first aspect, the high-strength crack-resistant mortar provided in the present application adopts the following technical solution: A high-strength anti-cracking mortar comprises the following raw materials in parts by weight: Cement: 100-120 parts; Recycled aggregate: 30-50 parts; Modified lightweight aggregate: 50-70 parts; Fly ash: 45-60 parts; Biomass ash: 15-20 parts; Alkali activator: 50-65 parts; Reinforcing fiber: 1.2-1.8 parts; Slow setting water reducing agent: 1.2-1.6 parts; Water: 45-50 parts; The recycled aggregate is made from waste concrete that is fully crushed and sieved to obtain coarse aggregate with a particle size of less than 2 mm, and is immersed in water to make it in a saturated surface dry state; the modified lightweight aggregate includes limestone, coal gangue and hollow glass microspheres mixed in proportion, and is obtained by calcining and mixing with diatomaceous earth in a hydrophobic emulsion; the reinforcing fiber includes any one of polyvinyl alcohol fiber and polyacrylonitrile fiber.
[0007] By adopting the above technical scheme, the hollow glass microspheres are modified with limestone, coal gangue, diatomaceous earth and hydrophobic emulsion to obtain modified lightweight aggregate, and then the modified lightweight aggregate is used to replace the conventional recycled aggregate, which can not only effectively improve the fluidity of the mortar, but also greatly reduce the density of the concrete after the mortar is cured, and has good construction performance, which is conducive to making the mortar more suitable for application in 3D printing construction slurry. At the same time, with reinforcing fibers, specific volcanic ash materials and alkali activators, even if the modified lightweight aggregate replaces 50%-70% of the recycled aggregate, the formed concrete can still maintain more than 80% of the mechanical strength of the concrete before replacement, with good compressive strength and flexural strength, which is conducive to the formation of lightweight, high-strength and crack-resistant concrete.
[0008] Optionally, the method for preparing the modified lightweight aggregate comprises the following steps: A1. First, limestone and coal gangue are mixed in a weight ratio of 1: (2-3), and then fully crushed to a particle size of less than 0.2 mm to obtain a mixed powder, and then hollow glass microspheres are added and mixed for 4-5 minutes to obtain a primary mixed lightweight aggregate, wherein the weight ratio of the mixed powder to the hollow glass microspheres is 1: (1-1.5); A2. The primary mixed lightweight aggregate obtained in step A1 is slowly heated to 850° C.-900° C. within 2 hours, and the temperature is maintained for continuous roasting for 2-3 hours. After cooling, it is immersed in a hydrophobic emulsion, and then diatomaceous earth is added and stirred and mixed again for 1-2 hours, and then allowed to stand for 3-4 hours. The filter residue is filtered under reduced pressure and naturally air-dried, and the filter residue is crushed again until its average particle size is less than 0.2 mm to obtain a modified lightweight aggregate.
[0009] By adopting the above technical scheme, when the crushed limestone and coal gangue are fully mixed with the hollow glass microspheres and then calcined at high temperature, quicklime and a small amount of kaolin will be produced respectively to coat the surface of the hollow glass microspheres, and then added into the hydrophobic emulsion together with diatomaceous earth. The water in the hydrophobic emulsion will induce the quicklime to generate calcium hydroxide, and react with the kaolin to produce volcanic ash in the hydrophobic emulsion to form a colloid, so that the diatomaceous earth and other hydration products can be fully adhered to and coated on the surface of the hollow glass microspheres, and a mixed lightweight aggregate with a highly porous surface is re-formed. At the same time, the mixed lightweight aggregate can also serve as a carrier to fully adsorb the polymethylhydrogensiloxane in the hydrophobic emulsion, which can further improve the surface hydrophobicity of the mixed lightweight aggregate, and effectively reduce the overall water absorption rate and permeability of the aggregate, which is beneficial to improve the density, mechanical strength and impermeability of the concrete.
[0010] Optionally, the hydrophobic emulsion is specifically prepared by dispersing and mixing polymethylhydrogensiloxane and water in a weight ratio of 1:(3-4).
[0011] By adopting the above technical scheme, polymethylhydrogensiloxane is fully dispersed in water as a hydrophobic agent to form a hydrophobic emulsion, which can be coated on the surface of the modified lightweight aggregate by adsorption or reaction, thereby further improving the surface hydrophobicity of the modified lightweight aggregate. When the modified lightweight aggregate replaces part of the recycled aggregate, it can effectively reduce the overall water absorption and permeability of the aggregate, thereby helping to improve the density, mechanical strength and impermeability of the concrete.
[0012] Optionally, in step A2, the weight ratio of the primary mixed lightweight aggregate, the hydrophobic emulsion and the diatomaceous earth is 1:2:(0.4-0.6).
[0013] By adopting the above technical solution, at this mixing ratio, it is beneficial to obtain a modified lightweight aggregate with suitable density, porosity, hydrophobicity and comprehensive performance.
[0014] Optionally, the reinforcing fibers are specifically selected from polyvinyl alcohol fibers, and the average length of the polyvinyl alcohol fibers is 5-12 mm.
[0015] By adopting the above technical solution, the polyvinyl alcohol fiber has good alkali resistance, and can maintain its reinforcement effect for a long time in the high alkaline system of the technical solution, which is conducive to maintaining the mechanical properties of concrete and improving the durability of concrete. Secondly, at this length of the polyvinyl alcohol fiber, the mortar can have high fluidity, and the concrete formed after curing also has good flexural strength.
[0016] Optionally, the alkaline activator is specifically selected from a sodium silicate solution, wherein the mass fraction of Na2O in the sodium silicate solution is 12.8%, and the molar ratio of SiO2 and Na2O in the sodium silicate solution is adjusted to 1.6-2 by sodium hydroxide.
[0017] By adopting the above technical solution, when the modulus of the sodium silicate solution is between 1.6 and 2, not only the mortar has higher fluidity, but also the concrete after the mortar is cured has good mechanical strength.
[0018] Optionally, the biomass ash is one of a mixture of rice husk ash and corn straw ash, a mixture of rice husk ash and bagasse ash, and a mixture of rice husk ash, corn straw ash and bagasse ash.
[0019] By adopting the above technical scheme, since the phosphate content in corn straw ash and bagasse ash is relatively high, a small amount of phosphate can not only promote the hydration reaction of cement and improve the density and mechanical strength of concrete. When the biomass ash is specifically selected to be mixed with rice husk ash and any one of corn straw ash or bagasse ash, it is beneficial to improve the mechanical strength of concrete, and at the same time has little effect on the fluidity of mortar and the density of concrete.
[0020] Optionally, the retarding water reducer is mixed and compounded by a high-efficiency water reducer, a hydroxycarboxylate and a non-ionic cellulose ether in a weight ratio of 1:(0.1-0.14):(0.06-0.15), wherein the high-efficiency water reducer includes any one of a polycyclic aromatic sulfonate water reducer or an aminosulfonate water reducer; the hydroxycarboxylate includes at least one of sodium citrate or sodium tartrate; and the cellulose ether includes any one of hydroxypropyl cellulose and hydroxypropyl carboxymethyl cellulose.
[0021] By adopting the above technical solution, it is beneficial to reduce the water-cement ratio, improve the mechanical strength of concrete, and appropriately prolong the mortar setting time so that the mortar can fully flow and extrude, which is beneficial to further improve the adaptability of mortar applications in 3D printing building slurries.
[0022] In the second aspect, the present application provides a method for preparing a high-strength crack-resistant mortar using the following technical solution: A method for preparing high-strength crack-resistant mortar comprises the following steps: S1. First, cement, recycled aggregate, modified lightweight aggregate, fly ash, biomass ash and slow-setting water-reducing agent are fully mixed at a stirring speed of 120r / min-150r / min for 1-2min, 95% by weight of water is added, and the stirring speed is maintained and continued until the mixture reaches a flowable state, and then the stirring speed is increased to 250r / min-300r / min, and stirring is continued for 3-5min to obtain a first slurry; S2. Slowly add an alkali activator to the first slurry, and continue stirring at a stirring speed of 250 r / min-300 r / min for 10-15 min to obtain a second slurry; S3. Add reinforcing fibers and the remaining water to the second slurry, and continue stirring at a stirring speed of 250 r / min-300 r / min for 5-10 min to obtain a high-strength crack-resistant mortar.
[0023] By adopting the above technical solution, it is conducive to fully mixing solid materials such as cement, recycled aggregate, modified lightweight aggregate, fly ash, biomass ash, etc., and obtaining mortar with high fluidity and good extrusion performance. Secondly, the preparation method of mortar is simple and convenient, which is conducive to mass production and preparation.
[0024] In the third aspect, the application of a high-strength anti-crack mortar provided in the present application adopts the following technical solution: Application of high-strength crack-resistant mortar in 3D printing technology.
[0025] In summary, the technical solution of this application has at least one of the following beneficial effects: 1. The hollow glass microspheres are modified by using limestone, coal gangue, diatomaceous earth and hydrophobic emulsion to obtain modified lightweight aggregate, and then the modified lightweight aggregate is used to replace the conventional recycled aggregate. It can not only effectively improve the fluidity of the mortar, but also greatly reduce the density of the concrete after the mortar is cured. It has good construction performance and is conducive to making the mortar more suitable for application in 3D printing construction slurry.
[0026] 2. By using modified lightweight aggregate in combination with reinforcing fibers, specific volcanic ash materials and alkali activators, even if the modified lightweight aggregate replaces 50%-70% of the recycled aggregate, the formed concrete can still maintain more than 80% of the mechanical strength of the concrete before replacement, and has good compressive strength and flexural strength, which is conducive to the formation of lightweight, high-strength and crack-resistant concrete. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in combination with preparation examples, embodiments, comparative examples and application examples.
[0028] The hollow glass microspheres were purchased from Zhongke Huaxin, with a specific grade of C70. The true density of the hollow glass microspheres of this grade is 0.7-0.76 g / cm 3 .
[0029] The sodium silicate solution was purchased from Kening New Materials, and the specific brand was industrial grade sodium silicate solution-4, in which the mass fraction of Na2O in the sodium silicate solution of this brand was 12.8%, and the initial modulus was 2.2 (the modulus is the ratio of SiO2 to Na2O).
[0030] Preparation Example [Preparation Example 1] A modified lightweight aggregate is prepared by the following steps: A1. First, 5 kg of limestone and 10 kg of coal gangue were mixed, and then crushed by a pulverizer to a particle size of less than 0.2 mm to obtain a mixed powder; then 22.5 kg of hollow glass microspheres were added, and the mixture was fully mixed to obtain a primary mixed lightweight aggregate; A2. The primary mixed lightweight aggregate obtained in step A1 is slowly heated to 850° C. within 2 hours, and then the temperature is maintained for 3 hours. After cooling, it is immersed in a hydrophobic emulsion prepared by fully dispersing and mixing 15 kg of polymethylhydrogensiloxane and 60 kg of water, and then 22.5 kg of diatomaceous earth is added and stirred for 2 hours. The mixture is allowed to stand for 4 hours, and the residue is filtered under reduced pressure and naturally air-dried. The residue is crushed again and sieved to obtain a modified lightweight aggregate with an average particle size of less than 0.2 mm.
[0031] [Preparation Example 2] A modified lightweight aggregate is prepared by the following steps: A1. First, 5 kg of limestone and 15 kg of coal gangue were mixed, and then crushed by a pulverizer to a particle size of less than 0.2 mm to obtain a mixed powder; then 20 kg of hollow glass microspheres were added, and the mixture was fully mixed to obtain a primary mixed lightweight aggregate; A2. The primary mixed lightweight aggregate obtained in step A1 is slowly heated to 900° C. within 2 hours, and then the temperature is maintained for 3 hours. After cooling, it is immersed in a hydrophobic emulsion prepared by fully dispersing and mixing 20 kg of polymethylhydrogensiloxane and 60 kg of water, and then 16 kg of diatomaceous earth is added and stirred for 1 hour. The mixture is allowed to stand for 3 hours, and the residue is filtered under reduced pressure and naturally air-dried. The residue is crushed again until its average particle size is less than 0.2 mm to obtain a modified lightweight aggregate. Example
[0032] [Example 1] A high-strength crack-resistant mortar comprises the following raw materials: 100 kg of cement, 50 kg of recycled aggregate, 50 kg of modified lightweight aggregate, 60 kg of fly ash, 15 kg of biomass ash, 50 kg of alkali activator, 1.2 kg of reinforcing fiber, 1.2 kg of slow-setting water-reducing agent and 50 kg of water.
[0033] The recycled aggregate is made of waste concrete that is fully crushed and sieved to obtain coarse aggregate with an average particle size of less than 2 mm, and then immersed in water to make it in a saturated surface dry state.
[0034] Among them, the modified lightweight aggregate is specifically selected from a modified lightweight aggregate prepared in [Preparation Example 1].
[0035] The biomass ash is specifically selected from rice husk ash; the alkaline activator is specifically selected from sodium silicate solution, and the modulus of the sodium silicate solution is adjusted to 2 by using sodium hydroxide.
[0036] The reinforcing fibers are specifically selected from polyvinyl alcohol fibers, and the average length of the reinforcing fibers is 12 mm.
[0037] The retarding water reducer is specifically prepared by mixing polycyclic aromatic sulfonate water reducer, sodium citrate and hydroxypropyl cellulose in a weight ratio of 1:0.14:0.06, that is, the retarding water reducer includes 1 kg polycyclic aromatic sulfonate water reducer, 0.14 kg sodium citrate and 0.06 kg hydroxypropyl carboxymethyl cellulose. In this embodiment, the polycyclic aromatic sulfonate water reducer is specifically selected from sodium β-naphthalenesulfonate.
[0038] A method for preparing high-strength crack-resistant mortar comprises the following steps: S1. First, cement, recycled aggregate, modified lightweight aggregate, fly ash, biomass ash and slow-setting water-reducing agent are fully mixed at a stirring speed of 120 r / min for 2 min, 95% by weight of water is added, and the stirring speed is maintained and continued to be stirred until the mixture reaches a flowable state, and then the stirring speed is increased to 300 r / min and stirred for 3 min to obtain a first slurry; S2. Slowly add the alkali activator to the first slurry, and continue stirring at a stirring speed of 300 r / min for 10 min to obtain the second slurry.
[0039] S3. Add reinforcing fibers and the remaining water to the second slurry, and continue stirring at a stirring speed of 300 r / min for 5 minutes to obtain a high-strength crack-resistant mortar.
[0040] [Example 2] A high-strength crack-resistant mortar comprises the following raw materials: 120 kg of cement, 30 kg of recycled aggregate, 70 kg of modified lightweight aggregate, 45 kg of fly ash, 20 kg of biomass ash, 65 kg of alkali activator, 1.8 kg of reinforcing fiber, 1.6 kg of slow-setting water-reducing agent and 45 kg of water.
[0041] The recycled aggregate is made of waste concrete that is fully crushed and sieved to obtain coarse aggregate with an average particle size of less than 2 mm, and then immersed in water to make it in a saturated surface dry state.
[0042] Among them, the modified lightweight aggregate is specifically selected from a modified lightweight aggregate prepared in [Preparation Example 2].
[0043] The biomass ash is specifically selected from rice husk ash and corn straw ash mixed in a weight ratio of 1:1, namely, including 15kg of rice husk ash and 15kg of corn straw ash.
[0044] The alkaline activator is specifically a sodium silicate solution, and the modulus of the sodium silicate solution is adjusted to 1.6 using sodium hydroxide.
[0045] The reinforcing fiber is specifically selected from polyacrylonitrile fibers, and the average length of the reinforcing fibers is 5 mm.
[0046] The retarding water reducer is specifically prepared by mixing aminosulfonate-based high-efficiency water reducer, sodium citrate, sodium tartrate and hydroxypropyl cellulose in a weight ratio of 1:0.08:0.02:0.15, that is, the retarding water reducer includes 1.28kg aminosulfonate-based high-efficiency water reducer, 0.102kg sodium citrate, 0.026kg sodium tartrate and 0.192kg hydroxypropyl cellulose. Specifically, the aminosulfonate-based high-efficiency water reducer is specifically selected as brand SSF-3000.
[0047] A method for preparing high-strength crack-resistant mortar comprises the following steps: S1. First, cement, recycled aggregate, modified lightweight aggregate, fly ash, biomass ash and slow-setting water-reducing agent are fully mixed at a stirring speed of 150 r / min for 1 min, 95% by weight of water is added, and the stirring speed is maintained and continued until the mixture reaches a flowable state, and then the stirring speed is increased to 250 r / min and the stirring is continued for 5 min to obtain a first slurry; S2, slowly adding an alkali activator to the first slurry, and continuing stirring at a stirring speed of 250 r / min for 15 min to obtain a second slurry; S3. Add reinforcing fibers and the remaining water to the second slurry, and continue stirring at a stirring speed of 250 r / min for 10 minutes to obtain a high-strength crack-resistant mortar.
[0048] [Example 3] A high-strength crack-resistant mortar, which differs from [Example 1] in that the added amounts of recycled aggregate and modified lightweight aggregate are different.
[0049] In this embodiment, the amount of recycled aggregate added is 30 kg, and the amount of modified lightweight aggregate added is 70 kg.
[0050] [Example 4] A high-strength crack-resistant mortar, which differs from [Example 1] in that the added amounts of recycled aggregate and modified lightweight aggregate are different.
[0051] In this embodiment, the amount of recycled aggregate added is 10 kg, and the amount of modified lightweight aggregate added is 90 kg.
[0052] [Example 5] A high-strength crack-resistant mortar, which differs from [Example 3] in that the composition of biomass ash is different.
[0053] In this embodiment, the biomass ash is a mixture of rice husk ash and corn straw ash in a weight ratio of 1:0.5, that is, the biomass ash specifically includes 10 kg of rice husk ash and 5 kg of corn straw ash.
[0054] [Example 6] A high-strength crack-resistant mortar, which differs from [Example 3] in that the composition of biomass ash is different.
[0055] In this embodiment, the biomass ash is a mixture of rice husk ash and bagasse ash in a weight ratio of 1:0.5, that is, the biomass ash specifically includes 10 kg of rice husk ash and 5 kg of bagasse ash.
[0056] [Example 7] A high-strength anti-cracking mortar, which differs from [Example 6] in that the modulus of the alkali activator is different.
[0057] In this embodiment, the modulus of the sodium silicate solution in the alkaline activator is adjusted to 1.6 by sodium hydroxide.
[0058] [Example 8] A high-strength anti-cracking mortar, which differs from [Example 6] in that the modulus of the alkali activator is different.
[0059] In this embodiment, the modulus of the sodium silicate solution in the alkaline activator is adjusted to 1.2 by sodium hydroxide.
[0060] [Example 9] A high-strength crack-resistant mortar, which differs from [Example 7] in that the reinforcing fibers are different.
[0061] In this embodiment, the reinforcing fibers are specifically selected from polyvinyl alcohol fibers, and the average length of the polyvinyl alcohol fibers is 5 mm.
[0062] [Example 10] A high-strength crack-resistant mortar, which differs from [Example 7] in that the reinforcing fibers are different.
[0063] In this embodiment, the reinforcing fiber is specifically selected from polyacrylonitrile fibers, and the average length of the polyacrylonitrile fibers is 12 mm.
[0064] Comparative Example [Comparative Example 1] A mortar, which differs from [Example 1] in that no modified lightweight aggregate is added.
[0065] In this comparative example, the modified lightweight aggregate is replaced in equal amounts by fine aggregates obtained by fully crushing and sieving waste concrete to obtain an average particle size of less than 0.2 mm.
[0066] [Comparative Example 2] A mortar, which differs from [Example 1] in that no modified lightweight aggregate is added.
[0067] In this comparative example, the modified lightweight aggregate was replaced by hollow glass microspheres in equal amounts.
[0068] [Comparative Example 3] A mortar, which differs from [Example 1] in that no reinforcing fiber is added.
[0069] Application Examples [Application Example 1] - [Application Example 10] A 3D printing building slurry, which is a high-strength crack-resistant mortar prepared by [Example 1] to [Example 10] in sequence.
[0070] Performance test data Preparation of the sample to be tested: Referring to GB / T 17671-2021 Cement Mortar Strength Test Method (ISO Method), the mortar prepared in each embodiment and comparative example is further made into a standard sample of 40mm*40mm*160mm. After 1 day, the standard sample is demoulded, and it is fully immersed in water and then covered with a film for curing to obtain the sample to be tested. The curing temperature is room temperature 26°C, the curing time is 28 days, and no water replenishment and humidity control are performed during the curing process to simulate a non-ideal simulation environment.
[0071] 1. Mortar fluidity: refer to "GB / T 2419-2005 Cement mortar fluidity determination method" for testing, and record the fluidity (mm) of the mortar of each embodiment and comparative example.
[0072] 2. Density test: The samples to be tested that have been cured for 28 days were weighed, and the concrete density (kg / m 3 ).
[0073] 3. Mechanical properties test: refer to “GB / T 17671-2021 Cement mortar strength test method (ISO method)” to test the samples that have been cured for 28 days, and record the concrete compressive strength (MPa) and flexural strength (MPa) of the mortar of each embodiment and comparative example after curing.
[0074] Table 1 Partial performance test data of mortar Fluidity mm <![CDATA[Density kg / m 3 > Compressive strength MPa Flexural strength MPa Example 1 211 1507 48.1 4.7 Example 2 186 1466 44.7 4.4 Example 3 220 1472 46.3 4.6 Example 4 226 1449 40.0 3.9 Example 5 221 1475 47.1 4.7 Example 6 219 1473 47.6 4.8 Example 7 213 1498 51.6 5.2 Example 8 202 1512 45.8 4.4 Example 9 220 1500 51.7 5.0 Example 10 214 1598 50.5 4.6 Comparative Example 1 162 1978 65.2 6.8 Comparative Example 2 235 1380 37.2 4.2 Comparative Example 3 216 1506 47.9 3.2 Combining Example 1 with Comparative Examples 1-3 and the data in Table 1, it can be seen that under the same water-cement ratio, by using the modified lightweight aggregate obtained by modifying the hollow glass microspheres to replace part of the conventional recycled aggregate, not only can the fluidity of the mortar be increased to more than 180 mm, so that the mortar can reach a state of easy flow and convenient printing and extrusion, but also the density of the mortar after solidification is greatly reduced, which is conducive to reducing the load-bearing requirements of the printing equipment and making the mortar more suitable for application in 3D printing building slurry. At the same time, through the cooperation between the modified lightweight aggregate and the reinforcing fiber in the mortar, the cured concrete can maintain more than 80% of the mechanical properties of the concrete without adding the modified lightweight aggregate, and has good compressive strength and flexural strength, thereby forming a lightweight, high-strength, crack-resistant concrete.
[0075] Specifically, it can be seen from Example 1 and Comparative Example 2 that by modifying the hollow glass microspheres with limestone, coal gangue, diatomaceous earth and hydrophobic emulsion, the modified lightweight material prepared is compared with ordinary hollow microspheres. Although adding the modified lightweight material to the mortar will cause the fluidity of the mortar to decrease and the density to increase, the mortar can have higher mechanical properties after curing. This may be because when the crushed limestone and coal gangue are fully mixed with the hollow glass microspheres and then calcined at high temperature, quicklime and a small amount of kaolin will be produced respectively to coat the surface of the hollow glass microspheres, and then added to the hydrophobic emulsion together with diatomaceous earth. The water in the hydrophobic emulsion will induce the quicklime to generate calcium hydroxide, and react with the kaolin to produce volcanic ash in the hydrophobic emulsion to form a colloid, so that the diatomaceous earth and other hydration products can fully adhere to and coat the surface of the hollow glass microspheres, re-forming a mixed lightweight aggregate with a highly porous surface. At the same time, the mixed lightweight aggregate can also serve as a carrier to fully adsorb the polymethylhydrogensiloxane in the hydrophobic emulsion, which can further improve the surface hydrophobicity of the mixed lightweight aggregate. Therefore, when the modified lightweight aggregate with high porosity and surface hydrophobicity is added to the mortar as a recycled aggregate instead of lightweight aggregate, it can reduce the water absorption and permeability of the aggregate, and thus improve the density, mechanical strength and impermeability of the concrete. However, due to their light weight and large slurry flow, unmodified hollow glass microspheres are easily separated due to buoyancy during mortar pumping and extrusion, resulting in poor mixing effect.
[0076] Combining Example 1 with Example 3-4 and the data in Table 1, it can be seen that by replacing conventional recycled aggregate with modified lightweight aggregate, as the proportion of modified lightweight aggregate in the mortar increases, the density and mechanical properties of the concrete after the mortar is cured will gradually decrease, and its flow properties will also increase accordingly. However, when the proportion of modified lightweight aggregate exceeds 70% of the total weight of the aggregate, the mechanical properties of the concrete will drop sharply, which may lead to its mechanical properties being too low. Therefore, when the ratio of recycled aggregate to modified lightweight aggregate is (3-5): (5-7), the comprehensive performance of the slurry is better and is more suitable for application in 3D printing construction slurry.
[0077] Combining Example 3 with Example 5-6 and the data in Table 1, it can be seen that when the biomass ash is specifically selected from rice husk ash and any one of corn straw ash or bagasse ash, it can improve the mechanical strength of concrete by a small amount compared with using rice husk ash alone, and has little effect on its density and fluidity. This may be because both corn straw ash and bagasse ash contain high levels of phosphate, and a small amount of phosphate can not only promote the hydration reaction of cement, improve the compactness and mechanical strength of concrete, but also form insoluble phosphate precipitation with alkaline substances in concrete, reduce alkali-aggregate reaction, and thus help improve the performance and durability of concrete.
[0078] Combining Examples 6-8 and the data in Table 1, it can be seen that when the modulus of the sodium silicate solution in the alkali activator is adjusted from 2 to 1.6, the mechanical strength of the concrete increases accordingly, and when the modulus of the sodium silicate solution in the alkali activator is further reduced from 1.6 to 1.2, the mechanical strength of the concrete decreases sharply, and the fluidity of the mortar decreases with the decrease in the modulus. This may be because the modulus of the sodium silicate solution in the alkali activator is specifically SiO 2 with Na 2 O ratio. When the modulus of sodium silicate solution is higher than 1.6, as the modulus increases, the proportion of Na2O decreases, and the OH produced by the hydrolysis of sodium silicate solution - The amount will gradually decrease, making it difficult to stimulate the decomposition of fly ash or biomass ash, and SiO4 4- Due to the high concentration, the degree of polymerization increases and it is difficult to react with Ca 2+ Plasma reaction will reduce the strength of the hydration products formed and reduce the mechanical properties of concrete. When the modulus of sodium silicate solution is lower than 1.6, although the proportion of Na2O is high, a large amount of OH - It can promote the decomposition of fly ash and biomass ash, but also due to SiO4 4- The proportion is low, and the double excitation becomes a single excitation, which will also lead to the low strength of the hydration products formed, which will in turn affect the mechanical strength of the concrete.
[0079] Combining Example 7 with Examples 9-10 and the data in Table 1, it can be seen that by using shorter polyvinyl alcohol fibers as reinforcing fibers, the fluidity of the mortar is significantly improved, and the density and compressive strength of the concrete are not greatly affected, but the flexural strength of the concrete is slightly reduced.
[0080] In addition, when the polyvinyl alcohol fibers are replaced with polyacrylonitrile fibers of equal length, the mechanical strength of the concrete is significantly reduced. This may be because in the technical solution of the present application, an alkali activator is added to the mortar system, which belongs to a high alkaline system, and the alkali resistance of polyacrylonitrile fibers is poor. After 28 days of natural curing, the mixed polyacrylonitrile fibers may be corroded by the alkaline substances in the system, resulting in a significant weakening of their own reinforcement effect, thereby affecting the mechanical strength of the concrete.
[0081] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength anti-crack mortar, characterized in that: It includes the following raw materials in parts by weight: Cement: 100-120 parts; Recycled aggregate: 30-50 parts; Modified lightweight aggregate: 50-70 parts; Fly ash: 45-60 parts; Biomass ash: 15-20 parts; Alkali activator: 50-65 parts; Reinforcing fiber: 1.2-1.8 parts; Slow setting water reducing agent: 1.2-1.6 parts; Water: 45-50 parts; The recycled aggregate is made from waste concrete that is fully crushed and sieved to obtain coarse aggregate with a particle size of less than 2 mm, and is immersed in water to make it in a saturated surface dry state; the modified lightweight aggregate includes limestone, coal gangue and hollow glass microspheres mixed in proportion, and is obtained by calcining and mixing with diatomaceous earth in a hydrophobic emulsion; the reinforcing fiber includes any one of polyvinyl alcohol fiber and polyacrylonitrile fiber.
2. A high-strength anti-cracking mortar according to claim 1, characterized in that: The preparation method of the modified lightweight aggregate comprises the following steps: A1. First, limestone and coal gangue are mixed in a weight ratio of 1: (2-3), and then fully crushed to a particle size of less than 0.2 mm to obtain a mixed powder, and then hollow glass microspheres are added and mixed for 4-5 minutes to obtain a primary mixed lightweight aggregate, wherein the weight ratio of the mixed powder to the hollow glass microspheres is 1: (1-1.5); A2. The primary mixed lightweight aggregate obtained in step A1 is slowly heated to 850° C.-900° C. within 2 hours, and the temperature is maintained for continuous roasting for 2-3 hours. After cooling, it is immersed in a hydrophobic emulsion, and then diatomaceous earth is added and stirred and mixed again for 1-2 hours, and then allowed to stand for 3-4 hours. The filter residue is filtered under reduced pressure and naturally air-dried, and the filter residue is crushed again until its average particle size is less than 0.2 mm to obtain a modified lightweight aggregate.
3. A high-strength anti-cracking mortar according to claim 2, characterized in that: The hydrophobic emulsion is specifically prepared by dispersing and mixing polymethylhydrogensiloxane and water in a weight ratio of 1:(3-4).
4. A high-strength anti-cracking mortar according to claim 3, characterized in that: In step A2, the weight ratio of the primary mixed lightweight aggregate, the hydrophobic emulsion and the diatomaceous earth is 1:2:(0.4-0.6).
5. The high-strength anti-cracking mortar according to claim 1, characterized in that: The reinforcing fibers are specifically selected from polyvinyl alcohol fibers, and the average length of the polyvinyl alcohol fibers is 5-12 mm.
6. The high-strength anti-cracking mortar according to claim 1, characterized in that: The alkaline activator is specifically selected from sodium silicate solution, wherein the mass fraction of Na2O in the sodium silicate solution is 12.8%, and the molar ratio of SiO2 and Na2O in the sodium silicate solution is adjusted to 1.6-2 by sodium hydroxide.
7. The high-strength anti-cracking mortar according to claim 1, characterized in that: The biomass ash is one of a mixture of rice husk ash and corn straw ash, a mixture of rice husk ash and bagasse ash, and a mixture of rice husk ash, corn straw ash and bagasse ash.
8. The high-strength anti-cracking mortar according to claim 1, characterized in that: The retarding water reducer is prepared by mixing a high-efficiency water reducer, a hydroxycarboxylate and a nonionic cellulose ether in a weight ratio of 1: (0.1-0.14): (0.06-0.15), wherein the high-efficiency water reducer comprises any one of a polycyclic aromatic sulfonate water reducer or an aminosulfonate water reducer; the hydroxycarboxylate comprises at least one of sodium citrate or sodium tartrate; and the cellulose ether comprises any one of hydroxypropyl cellulose and hydroxypropyl carboxymethyl cellulose.
9. A method for preparing a high-strength anti-cracking mortar according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. First, cement, recycled aggregate, modified lightweight aggregate, fly ash, biomass ash and slow-setting water-reducing agent are fully mixed at a stirring speed of 120r / min-150r / min for 1-2min, 95% by weight of water is added, and the stirring speed is maintained and continued until the mixture reaches a flowable state, and then the stirring speed is increased to 250r / min-300r / min, and stirring is continued for 3-5min to obtain a first slurry; S2. Slowly add the alkali activator to the first slurry, and continue stirring at a stirring speed of 250 r / min-300 r / min for 10-15 min to obtain a second slurry; S3. Add reinforcing fibers and the remaining water to the second slurry, and continue stirring at a stirring speed of 250 r / min-300 r / min for 5-10 minutes to obtain a high-strength crack-resistant mortar.
10. Application of the high-strength crack-resistant mortar according to any one of claims 1 to 8 in 3D printing building slurry.